Μελέτη μηχανικής συμπεριφοράς ινοπλισμένου σκυροδέματος μετά από θερμική καταπόνηση - Παπαδημητρίου, Ευγενία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Οπλισμένου Σκυροδέματος, 2016)
The behavior of the concrete is characterized by its mechanical properties. In this diploma thesis we study the mechanical behavior of the fiber-reinforced concrete, both with metalic and synthetic fibers, at ambient and high temperatures (280°C). The test pieces were produced, by the same composition, and they defer due to the addition of different fibers volume concentration of 0.5% and 1.0%. The used metalic fibers of INOMIX type (SF) had anchors at the edges, while the synthetic SikaFiber® fibers were being of two types: a) macrofibres PP-540/52 (PPF1), b) microfibers (PPF2). All formulations were compared with the same reference composition without fibers and in all compositions silica fume was added. In addition to the classic characterization testing of fresh and hardened concrete properties, they were also determined the elastic modulus, the poisson ratio of fiber-reinforced concrete and the tensile strength of concrete through the Barcelona Test and through three points bending test, with notch. Finally through the tensile test, it was studied the post cracking behavior of the test specimens and it has been evaluated the fracture toughness of fiber reinforced concrete for each composition. Based on the results, the effect of temperature on compressive strength implies a reduction of 30%. In the composition PPF2-0.5 it was observed the lower impact which it was also replied by the elastic modulus. The relatively large variation of Poisson's ratio values, does not allow reaching safe conclusions about the effect of temperature. Based on the results, little change in toughness index in Barcelona test it was recorded for the compositions with metalic fibers. Indicatively, the change toughness index I1.5 after heat stress, ranges between 20-60% for the compositions with single synthetic fibers and for the hybrid compositions. In hybrid compositions the change of I1.5, was significant. Based on the results of three point bending test with notch, the smallest change in toughness index was recorded for the compositions with metalic fibers. On contrast, the change of toughness index I1.5 after the heat stress ranges between 70-90% for the single synthetic fibers’ compositions and for the hybrid compositions.